The burden of cardiovascular disease in Sub-Saharan Africa - Mbewu, Anthony (SA Heart Journal, 2017)
The burden of cardiovascular disease (CVD) in Africa is growing and changing in nature. From the predominance of rheumatic heart disease and cardiomyopathies 50 years ago to hypertensive heart disease and haemorrhagic stroke in the past 25 years. Albeit at low prevalence, an increase in incidence of ischaemic heart disease is now being seen, particularly in urban areas. These changes in the extent and nature of CVD are thought to be the result of the so-called “epidemiological transition”. The challenge for health promotion and prevention is to accelerate the course of that transition and blunt its magnitude in order to avoid the massive epidemics of CVD that were seen in Europe and the USA in the mid-twentieth century.